Representasi Feminisme Dalam Film Perempuan Tanah Jahanam - Swari Pidada, Ida Ayu Prita Dara; Sugiarica Joni, I Dewa Ayu; Pradipta, Ade Devia (E-Jurnal Medium, 2021)
Films unconsciously often create gender-biased relationships. Women are often placed in a weak and marginalized position. The film Perempuan Tanah Jahanam is one of the Indonesian films that dares to break the stereotype of women in society by raising the issue of feminism in its story. The main character in _ this _ film _ is shown as _ a strong and courageous woman. The aims of this study is to explain the representation of feminism in the film Perempuan Tanah Jahanam. This research uses qualitative approach with John Fiske's semiotic analysis method Television Codes. The results of this study indicate that the representation of feminism that is reflected through the four main female characters is postmodern feminism because they highlight how women can show their existence by being themselves. Postmodern feminism is reflected in women who are depicted as hard-working, dare to make decisions, fight sexual harassment, woman support woman, have a great love for family . Keywords: film Perempuan Tanah Jahanam, feminism, semiotic, John Fiske codes of televisions